Comparison of patients hospitalized with influenza A subtypes H7N9, H5N1, and 2009 pandemic H1N1. - Wang, C; Yu, H; Horby, P; Cao, B; Wu, P; Yang, S; Gao, H; Li, H; Tsang, T; Liao, Q; Gao, Z; Ip, D; et al. (University of Chicago Press, 2014)
BACKGROUND: Influenza A(H7N9) viruses isolated from humans show features suggesting partial adaptation to mammals. To provide insights into the pathogenesis of H7N9 virus infection, we compared risk factors, clinical presentation, and progression of patients hospitalized with H7N9, H5N1, and 2009 pandemic H1N1 (pH1N1) virus infections. METHODS: We compared individual-level data from patients hospitalized with infection by H7N9 (n = 123), H5N1 (n = 119; 43 China, 76 Vietnam), and pH1N1 (n = 3486) viruses. We assessed risk factors for hospitalization after adjustment for age- and sex-specific prevalence of risk factors in the general Chinese population. RESULTS: The median age of patients with H7N9 virus infection was older than other patient groups (63 years; P < .001) and a higher proportion was male (71%; P < .02). After adjustment for age and sex, chronic heart disease was associated with an increased risk of hospitalization with H7N9 (relative risk, 9.68; 95% confidence interval, 5.24-17.9). H7N9 patients had similar patterns of leukopenia, thrombocytopenia, and elevated alanine aminotransferase, creatinine kinase, C-reactive protein, and lactate dehydrogenase to those seen in H5N1 patients, which were all significantly different from pH1N1 patients (P < .005). H7N9 patients had a longer duration of hospitalization than either H5N1 or pH1N1 patients (P < .001), and the median time from onset to death was 18 days for H7N9 (P = .002) vs 11 days for H5N1 and 15 days for pH1N1 (P = .154). CONCLUSIONS: The identification of known risk factors for severe seasonal influenza and the more protracted clinical course compared with that of H5N1 suggests that host factors are an important contributor to H7N9 severity.